Accountability the case of the post-disaster coconut planting/replanting project in Lawaan, Eastern Samar (AY 2015-2016) - Ellema, Diana Grace A.; Obillo, Christine Joyce L.; Olaran, Maila L.; Brazas-Lim, Ladylyn (2016)
Our country has exhibited accountability deficits as presented in numerous studies and even in domestic and international indices. This is seen as a problem since the accountability is an important core principle of democracy and is crucial for a regime's stability and legitimacy. One of the challenges faced in the pursuit of an accountable government is during times of disaster. Despite widespread chaos and destruction, the national government should still be composed and stay accountable to the people, most especially the first responder that is the local government. The principle of accountability is embedded in the law, RA 10121 or the Philippine Disaster Risk Reduction and Management Law, and in legal framework for disaster response documents such as the Comprehensive Recovery and Rehabilitation Plan (CRRP) and the Reconstruction Assistance on Yolanda (RAY). This study aims to review the presence of accountability, more specifically its principles in the agend- setting, policy making, and implementation phase. The researchers utilized the case of the Coconut Planting/Replanting under the Philippine Coconut Authority (PCA) Yolanda Rehabilitation and Recovery Program (YRRP) in the five regular barangays of Lawaan, Eastern Samar. This research concludes with the observations seen during the service delivery and the recommendations deemed necessary to improve accountability in the local government.
Undergraduate thesis (B.A.S.S. Political Science ) -- University of the Philippines, Tacloban.
Keywords: Social Sciences